THE STUDY OF AL-ZAMAKHSARI IN EXPLAINING I'JAZ QURAN - Muhammad Amin Nurdin (Buletin Al-Turas, 1995)
When al-Qur'an was sent down to the Arab people, the bigger part of them did believe in it, while some did not believe that it is the revelation from God Himself Biog Amongst those who disbelieved actual they did know the aspects of i'jaz al-Qur'an. This was proved by the when they tried to match got u the eloquency of a Qur'an, wich then was b occured to be a failure.